IMPLEMENTASI PEMBELAJARAN IPAS BERBASIS KONTEKSTUAL DI SD NEGERI : STUDI KASUS PADA KELAS TINGGI SEKOLAH DASAR - Dewi, Adhisty Kirana; Rohani, Rohani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning of Natural and Social Sciences (IPAS) in elementary schools is often conducted through conventional instruction that mainly emphasizes theoretical explanations. As a result, the connection between the concepts taught and students’ real-life experiences is not always clearly established, which can limit students’ conceptual understanding and engagement in the learning process. Therefore, an instructional approach that links learning materials with authentic contexts is needed. This study aims to describe the implementation of contextual-based IPAS learning in upper elementary classes and to examine its influence on students’ learning engagement and conceptual understanding. The research employed a qualitative approach using a case study method conducted in an upper-grade class of a public elementary school. Data were collected through classroom observations, interviews with teachers and several students, and documentation of instructional materials. The collected data were analyzed using an interactive analysis technique consisting of data reduction, data display, and conclusion drawing. The findings indicate that contextual-based IPAS learning was implemented by connecting learning content with students’ daily experiences, utilizing the surrounding environment as a learning resource, and engaging students in discussion and problem-solving activities. This approach encouraged more active participation, fostered critical thinking, and supported students in developing a deeper and more meaningful understanding of IPAS concepts that can be applied in everyday life.